A simple route to 7-substituted Quinolin-2(1H)-ones from Meta-substituted anilines - Marisol Varela Ausec; Mary K. Payne; Jason R. Stewart; Olivia M. Galando; Eliott J. Wright; Sara E.S. Martin (Results in Chemistry)
Meta-substituted anilines are condensed with methyl 3,3-dimethoxypropionate in a two-step acylation, cyclization sequence to preferentially form 7-substituted quinolinones in an isomeric mixture with 5-substituted quinolinones. The product ratios in this previously unexplored class of substrates depend on the steric and electronic properties of the aniline substituent. Within a series of halogenated anilines, selectivity varies directly with electronegativity and inversely with C–X bond length, up to 93:7 (R = F). For alkyl substituted anilines, a Charton analysis reveals a linear free-energy relationship between steric bulk of the alkyl substituent and selectivity for 7-substituted products, where selectivity for 7-substituted products increases with steric bulk of the alkyl substituent. Alkyl substituted quinolinones are generated with up to 97:3 selectivity for the 7-substituted product when R = tBu.